Unmasking dermoscopic evaluation of melasma: findings of a cross-sectional study in central India - Sahana Sreenath; Yoganand J Phulari; Ravishekar N Hiremath; Sandhya Ghodke; Rishi Raj (Clinical Dermatology Review, 2022)
Background: There exists a wide range of variations in skin tone around the world, with Asian and Indian subjects showing a greater susceptibility toward pigmentation disorder. Objective: This study was carried out with the objective to assess the clinical and dermoscopic findings among different types of melasma in a single center of Central India. Materials and Methods: A cross-sectional study was carried out among patients with clinical features of melasma attending the outpatient department at multispecialty hospital with a sample size of 100. A prestructured pro forma was used to collect the baseline data. Clinical and dermatological examination was done after taking a detailed history. Clinical pattern of melasma such as centrofacial, malar, and mandibular was noted. The areas of melasma were examined using a contact polarized Dermlite DL4 3rd Gen Dermoscope attached to an iPhone. Results: The mean age of study participants was 38.15 years with a standard deviation of 6.93. Seventeen percentage were of male gender. Thirty-one percentage of the female patients had a history of oral contraceptive pill (OCP) usage, and 22% of the female patients had a history of menstrual abnormalities. Fitzpatrick skin Type IV was the most commonly affected skin type. Centrofacial type of melasma is the most common clinical type and reticuloglobular pattern is the commonly seen pattern on dermoscopy. The color of dermoscopy was predominantly brown in malar (52.2%) and mandibular (57.1%) and mixed in Centrofacial (45.7%), which was followed by 26.1%–28.6% mixed color in malar and andibular types and 41.4% brown color in centrofacial type. The difference in the color of dermoscopy (P = 0.48), presence of telangiectasia on dermoscopy (P = 0.23), pattern of dermoscopy (P = 0.15), and mean Melasma Severity Index scores with different clinical types was not statistically significant. Similarly, the association between different clinical types of melasma with duration of sun exposure (P = 0.33) and topical photo protection (P = 0.34) was also not statistically significant. Conclusion: Our study findings concluded that melasma is common in women in the age group of 27–56 years range. Exposure to sunlight and the hormonal changes (due to OCP usage) were those among the various factors influencing the development of melasma. Centrofacial melasma was the most common pattern seen in our study group. Epidermal melasma features on dermoscopy were reticuloglobular patterns with a brownish hue, while the features of dermal melasma were irregular patterns with a bluish hue and mixed melasma had irregular patchy brown pigmentation. Perifollicular globules and telangiectasia were also seen.